Is metacognition a causal moderator of the relationship between catastrophic misinterpretation and health anxiety? A prospective study. (March 2016) - Bailey, Robin; Wells, Adrian
Abstract: Psychological theories have identified a range of variables contributing to health anxiety, including, dysfunctional illness beliefs, catastrophic misinterpretation, somatosensory amplification and neuroticism. More recently, metacognitive beliefs have been proposed as important in health anxiety. This study aimed to test the potential causal role of metacognitive beliefs in health anxiety. A prospective design was employed and participants (n = 105) completed a battery of questionnaire at two time points (6 months apart). Results demonstrated that cognitive, personality and metacognitive variables were bi-variate prospective correlates of health anxiety. Hierarchical regression analysis revealed that only metacognitive beliefs emerged as independent and significant prospective predictors of health anxiety. Moderation analysis demonstrated that metacognitive beliefs prospectively moderated the relationship between catastrophic misinterpretation and health anxiety. Follow-up regression analysis incorporating the interaction term (metacognition × misinterpretation) showed that the term explained additional variance in health anxiety. The results confirm that metacognition is a predictor of health anxiety and it is more substantive than misinterpretations of symptoms, somatosensory amplification, neuroticism, and illness beliefs. These results may have major implications for current cognitive models and for the treatment of health anxiety. Highlights: We explore prospective associations, predictors, and moderators of health anxiety. All variables were bi-variate prospective correlates of health anxiety. Only metacognitive beliefs emerged as prospective predictors of health anxiety. Metacognitive beliefs prospectively moderated the relationship between catastrophic misinterpretation and health anxiety. Metacognitive beliefs may have a causal role in health anxiety.